Development of the Teacher’s Communicative Culture under the Conditions of Marital State: Challenges and Opportunities - Pyshchyk, Olena (Educological discourse, 2023)
The article focuses on the importance of communication etiquette and communication skills for teachers who work during martial law, because in such conditions teachers face a number of challenges that can affect the effectiveness of the educational process and the psychological well-being of students. Several key areas of development of the teacher's communicative culture in the conditions of martial law are considered. First of all, it emphasizes the importance of emotional intelligence, which helps teachers understand and control their emotions, and also helps build emotionally healthy relationships with students and colleagues. The second aspect to consider is active listening. Teachers must be attentive listeners, able to hear and understand their interlocutors. This helps to improve communication and establish an effective dialogue. The ability to adapt to new conditions and situations is important for teachers, especially during martial law. They must be flexible and able to quickly adapt to changes in order to ensure the continuity of the educational process and provide support to students in such difficult conditions. The teacher's communicative culture should be manifested not only in the classroom, but also in interaction in the social environment. It is noted that communication is the basis of professional and pedagogical interaction, which involves the exchange of information between communication subjects, as well as the assimilation of values, knowledge and methods of communicative activity. The key directions of the development of the communicative culture of the teacher in the conditions of martial law, which is an important component of the learning process, as it contributes to improving the quality of communication between the participants of the educational process, are considered. Martial law teachers should focus on developing emotional intelligence, active listening, effective conflict resolution, and adaptation to change. In conclusion, directions for the development of the teacher's communicative culture in the conditions of martial law are proposed. The development of these skills will help teachers communicate effectively with students, colleagues and other participants in the educational process, support a successful educational process and the psychological well-being of students.